An Exploratory Factor Analysis of a Brief Self-Report Scale to Detect Neurocognitive Impairment Among Participants Enrolled in Methadone Maintenance Therapy. - Copenhaver, Michael; Shrestha, Roman; Wickersham, Jeffrey A; Weikum, Damian; Altice, Frederick L (Journal of substance abuse treatment, 2016)
The present study examines the factor structure of the existing Neuropsychological Impairment Scale (NIS) through the use of exploratory factor analysis (EFA). The NIS is a brief, self-report measure originally designed to assess neurocognitive impairment (NCI) by having patients rate a range of items that may influence cognitive functioning. Stabilized patients on methadone maintenance therapy (MMT; N=339) in New Haven, CT who reported drug- or sex-related HIV risk behaviors in the past 6months were administered the full 95-item NIS. An EFA was then conducted using principal axis factoring and orthogonal varimax rotation. The EFA resulted in retaining 57 items, with a 9-factor solution that explained 54.8% of the overall variance. The revised 9-factor measure - now referred to as the Brief Inventory of Neuro-cognitive Impairment (BINI) - showed a diverse set of factors with excellent to good reliability (i.e., F1 α=0.97 to F9 α=0.73). This EFA suggests the potential utility of using the BINI in the context of addiction treatment. Further research should examine the utility of this tool within other clinical care settings.